2022
DOI: 10.3389/fimmu.2022.840246
|View full text |Cite
|
Sign up to set email alerts
|

Dihydronicotinamide Riboside Is a Potent NAD+ Precursor Promoting a Pro-Inflammatory Phenotype in Macrophages

Abstract: Nicotinamide adenine dinucleotide (NAD) metabolism plays an important role in the regulation of immune function. However, a complete picture of how NAD, its metabolites, precursors, and metabolizing enzymes work together in regulating immune function and inflammatory diseases is still not fully understood. Surprisingly, few studies have compared the effect of different forms of vitamin B3 on cellular functions. Therefore, we investigated the role of NAD boosting in the regulation of macrophage activation and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…NQO2 differs from NQO1 in that it requires NRH as a coenzyme [10]. NRH is a precursor of NAD [37] and increases intracellular NAD levels [38,39]. Our experiments showed that an increase in NQO2 following HOXA11-AS knockdown resulted in a decrease in NAD concentration.…”
Section: Discussionmentioning
confidence: 64%
“…NQO2 differs from NQO1 in that it requires NRH as a coenzyme [10]. NRH is a precursor of NAD [37] and increases intracellular NAD levels [38,39]. Our experiments showed that an increase in NQO2 following HOXA11-AS knockdown resulted in a decrease in NAD concentration.…”
Section: Discussionmentioning
confidence: 64%
“…NMN can also improve STRT1 function and cause alterations in macrophage phagocytosis and M1 polarization via the SIRT1, IL-17A, and Notch pathways ( Meng et al, 2021 ). Other studies have shown that NMN exerts neuroprotective effects by inhibiting neuronal apoptosis and death, delaying neuroinflammation, affecting macrophage polarization, and protecting the integrity of the blood-brain barrier ( Kitaoka et al, 2009 ; Wei et al, 2017a , b ; Harlan et al, 2019 ; Chen et al, 2020 ; Chini et al, 2022 ). SIRT2 is essential for LPS-induced microglial cell activation, and inhibiting SIRT2 can reduce microglial cell activation, alleviate neuroinflammation, decrease dopamine neuronal death, and delay Parkinson’s disease neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NMNH is the reduced form of NMN, which is converted to NAD + by NMNAT and inhibits glycolysis, the TCA cycle, and cell growth [ 29 ]. Surprisingly, NRH and NMNH increased NAD + levels to a much greater extent than NR and NMN [ 29 , 30 ].…”
Section: Extracellular Nad + Precursorsmentioning
confidence: 99%